2022
DOI: 10.1039/d2ra04726h
|View full text |Cite
|
Sign up to set email alerts
|

Recycling NR/SBR waste using probe sonication as a new devulcanizing method; study on influencing parameters

Abstract: In this work, a vulcanized blend of natural rubber (NR) and styrene butadiene rubber (SBR) (i.e. at weight ratio of 50 : 50) as a model for tire rubber was devulcanized using probe sonicationP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hence, rubber reclaiming is effective recycling method applied to the waste rubber tire. It uses mechanical, thermal, thermo-mechanical, chemo-thermomechanical, and irradiation energies to break down vulcanized bonds in vulcanized rubber networks [8]. The main rubber components of tires compose natural rubber (NR), butadiene rubber (BR), and styrene butadiene rubber (SBR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, rubber reclaiming is effective recycling method applied to the waste rubber tire. It uses mechanical, thermal, thermo-mechanical, chemo-thermomechanical, and irradiation energies to break down vulcanized bonds in vulcanized rubber networks [8]. The main rubber components of tires compose natural rubber (NR), butadiene rubber (BR), and styrene butadiene rubber (SBR) [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that σ, E b , cure rate index (CRI), M L, and M H were enhanced while t S2 and t C90 were reduced with the incorporation of a self-healing modifier in the NR/BR composite. Marzieh Shabani et al 15 examined the crumb particles (vitax 0.6, vitax 1.2, and diphenyl disulphide) blended with an NR/SBR (50/50) composite. It was noted that the CRI, M L , and M H were enhanced while the σ was decreased by the addition of vitax 0.6 in NR/SBR composites over other combinations.…”
Section: Introductionmentioning
confidence: 99%
“…devulcanization of the shell of particles) and devulcanization content improved by decrement in the particle size of the particles. Shabani et al 14 devulcanized NR/SBR waste by probe sonication and assessed the success of process using determination of sol/gel contents and crosslink densities before and after devulcanization. They also claimed that partial devulcanization occurred through probe sonication that its performance depend on the sonication power/time and chemical agent type.…”
Section: Introductionmentioning
confidence: 99%